Oligo-polyphenylenevinylene conjugated oligoelectrolyte membrane insertion molecules selectively disrupt cell envelopes of gram-positive bacteria - Hinks, Jamie (2015)
The modification of microbial membranes to achieve biotechnological strain improvement with exogenous small molecules such as oligo-polyphenylene (OPV) conjugated oligoelectrolyte (COE) membrane insertion molecules (MIMs) is an emerging biotechnological field. Little is known about the interactions of OPV COEs with their target – the bacterial envelope. We studied the toxicity of three previously reported OPV COES with a selection of Gram-negative and Gram-positive organisms and demonstrated that Gram-positive bacteria are more sensitive to OPV COEs than Gram-negative organisms. Transmission Electron Microscopy demonstrated that these MIMs disrupt microbial membranes and that this occurred to a much greater degree in Gram-positive-organisms. We used a number of mutants to probe the nature of MIM interactions with the microbial envelope but were unable to align the membrane perturbation effect of these compounds to previously reported membrane disruption mechanisms of, for example, cationic antimicrobial peptides. Instead the data support the notion that OPV COEs disrupt microbial membranes through a suspected interaction with diphosphatidylglycerol (DPG), a major component of Gram-positive membranes. The integrity of model membranes containing elevated amounts of DPG was disrupted to a greater extent by MIMs than those prepared from E. coli total lipid extracts alone.